2014
DOI: 10.14202/vetworld.2014.299-305
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reaction and toxicity caused by commonly used antimicrobials in canine practice

Abstract: An adverse drug reaction (ADR) is a serious concern for practicing veterinarians and other health professionals, and refers to an unintended, undesired and unexpected response to a drug that negatively affects the patient's health. It may be iatrogenic or genetically induced, and may result in death of the affected animal. The ADRs are often complicated and unexpected due to myriad clinical symptoms and multiple mechanisms of drug-host interaction. Toxicity due to commonly used drugs is not uncommon when they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In the animals reported the diagnostic was based on clinical findings and time of lesion evolution after appeared days after the beginning of antibiotic administration, since there was not allergic tests for clavulanate-amoxycillin in clinical practice. The treatment is based on discontinuing the therapy and if necessary replacing the drug with another pharmacological class [1,4,7]. The glucocorticoid use or anti histamine may be indicated depending on the type of clinical manifestations presented.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the animals reported the diagnostic was based on clinical findings and time of lesion evolution after appeared days after the beginning of antibiotic administration, since there was not allergic tests for clavulanate-amoxycillin in clinical practice. The treatment is based on discontinuing the therapy and if necessary replacing the drug with another pharmacological class [1,4,7]. The glucocorticoid use or anti histamine may be indicated depending on the type of clinical manifestations presented.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antibiotics can lead to adverse reactions concomitant or subsequent to treatment, alteration known as pharmacodermia. In human patients, is a high incidence disease, which are affected in about 10-20% of patients treated with antibiotics, being considered the fifth major cause of mortality [4,5]. In veterinary medicine it is suggested that the casuistry may be underestimated, due to similarity with several skin diseases [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations